Analisis aspek stilistika novel Home Sweet Loan karya Almira Bastari - Bagiya Bagiya; Krista Mutiara Wijayanti (Universitas Sarjanawiyata Tamansiswa, 2023)
Penelitian ini bertujuan mendeskripsikan (1) Diksi, (2) majas, dan (3) citraan dalam novel Home Sweet Loan karya Almira Bastari. Sumber data berupa novel Home Sweet Loan karya Almira Bastari. Jenis penelitian ini adalah deskriptif kualitatif. Data berupa dialog antartokoh dalam novel Home Sweet Loan karya Almira Bastari. Pengumpulan data dilakukan teknik simak dan catat. Analisis data dilakukan dengan teknik analisis isi. Metode penyajian hasil data berupa teknik informal. Hasil penelitian dapat disimpulkan bahwa aspek stilistika novel Home Sweet Loan meliputi: (1) Diksi, penggunaan kosa kata dalam novel Home Sweet Loan karya Almira Bastari meliputi: (a) bahasa Inggris, (b) bahasa Indonesia. (2) jenis majas yang digunakan penulis dalam novel Home Sweet Loan meliputi: (a) majas alegori, (b) majas eufimisme, (c) majas sarkasme. (3) citraan yang digunakan penulis dalam novel Home Sweet Loan meliputi: (a) citraan penglihatan. Penulis menggunakan diksi,majas, dan citraan berfungsi sebagai media untuk memperkuat pesan atau efek yang ingin disampaikan pada pembaca. Analysis of the stylistic aspects of the novel Home Sweet Loan by Almira Bastari Abstract: This study aims to describe (1) diction, (2) figurative language, and (3) imagery in Almira Bastari's novel Home Sweet Loan. The data source is the novel Home Sweet Loan by Almira Bastari. This type of research is descriptive qualitative. The data is in the form of a dialogue between characters in the novel Home Sweet Loan by Almira Bastari. In collecting data, observing and note-taking techniques were carried out. Data analysis was performed using content analysis techniques. The method of presenting data results is in the form of informal techniques. Based on the research results, it can be concluded that the stylistic aspects of the novel Home Sweet Loan include: (1) Diction, the use of vocabulary in the novel Home Sweet Loan by Almira Bastari includes: (a) English. (2) the types of figure of speech used by the author in Home Sweet Loan include (a) allegory, (b) euphemism, (c) sarcasm. (3) the imagery used by the author in Home Sweet Loan includes (a) visual imagery. The author uses diction, figure of speech, and imagery to function as a medium to strengthen the message or effect he wants to convey to the reader.